1989
DOI: 10.2135/cropsci1989.0011183x002900030048x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Alfalfa Divergently Selected for Herbage Lignin Concentration

Abstract: Programs to improve alfalfa (Medicago sativa L.) nutritive value have used selection criteria based on total herbage cell‐wall composition. There is only limited information addressing the effect of total‐herbage based phenotypic selection on changes in dry‐matter partitioning of the plant and on the nutritive value of plant parts. The objective of this study was to determine the effects of divergent herbage selection for alfalfa cell‐wall components on plant morphology. Two groups of germplasm were observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
2
21
2
Order By: Relevance
“…1a). This suggests that selection on the basis of one of the nutritive value parameters would affect LWR, which agrees with other studies (Kephart et al 1989).…”
Section: Relationship Among Variatessupporting
confidence: 92%
See 1 more Smart Citation
“…1a). This suggests that selection on the basis of one of the nutritive value parameters would affect LWR, which agrees with other studies (Kephart et al 1989).…”
Section: Relationship Among Variatessupporting
confidence: 92%
“…Several studies also reported no correlation or weak correlations between digestibility and DMY when cultivars or lines were compared on a single sampling date corresponding to a normal harvesting date (Heinrichs et al 1969;Hill and Barnes 1977;Sunberg et al 1983;Coors et al 1986;Julier and Huyghe 1997). Other studies, however, reported a reduced forage DMY as a result of selection for improved nutritive quality (Kephart et al 1989).…”
Section: Relationship Among Variatesmentioning
confidence: 99%
“…Breeding alfalfa for increased digestibility is a promising means to increase the nutritive value of forages (4,10,11,14,20,21,23). Both public and private alfalfabreeding programs routinely employ ADL as a selection criterion that is related to digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…An important fraction of the potential energy from alfalfa forage is unusable by ruminants due to the limited digestibility of cell walls (4,5,(7)(8)(9)(10)23). The plant cell wall is a complex matrix composed of polysaccharides, proteins, phenolics (including lignin), water, and minerals (7).…”
Section: Additional Keyword: Disease Componentsmentioning
confidence: 99%
“…Direct selection in forages for cell wall components has been conducted less frequently than for IVDMD or NDF concentration. Alfalfa was selected for low and high ADL concentrations (Hill 1981), but because selection was imposed on total herbage the observed changes in ADL were primarily caused by shifts in leaf-to-stem ratio between the low and high ADL selection lines (Kephart et al 1989(Kephart et al 1990. Selection in corn or maize (Zea mays L.) vegetative tissue for divergent concentrations of ADF resulted in genetic alteration of NDF, ADF, and ADL concentrations for both leaf sheath and stem tissues (Buendgen et al 1990).…”
Section: Modification Of Switchgrass Biomass Quality Via Traditional mentioning
confidence: 99%